Evaluation of Six Patients with Chromosome 18 Structural Anomalies and Novel Findings - Esra Işık; Bilcağ Akgün; Tahir Atik; Ferda Özkınay; Özgür Çoğulu (Galenos Yayinevi, 2020)
Aim:Structural chromosome 18 anomalies are characterized by multiple congenital anomalies and intellectual disability. In this study, 6 cases with structural anomalies of chromosome 18 diagnosed by using conventional and molecular cytogenetic analyses are presented.Materials and Methods:Six cases who were carrying structural chromosome 18 abnormalities were enrolled in the study. Developmental milestones, growth parameters and dysmorphologic features were evaluated by experienced clinical geneticists. Laboratory analysis including genetic tests, imaging studies, and eye and hearing examinations were obtained from the medical records, retrospectively.Results:All cases had karyotype analysis, 2 cases had fluorescence in situ hybridization analysis and one case had microarray analysis, which were performed by using peripheral blood. A total of 6 cases in which del (18p) in one case, del (18q) in 4 cases and i (18q) in one case were evaluated.Conclusion:Although a wide range of phenotypic findings, depending on the affected chromosomal region and size, can be seen in patients who carry structural chromosome 18 anomalies, some additional novel features are presented in our series which will contribute to the literature.